Aluminium bronze-steel sliding contact in packaging applications: Failure analysis and lab-scale tribological tests. (May 2020) - Boromei, I.; Ceschini, L.; Martini, C.; Sola, R.
Highlights: Components for pressing device in counterformal line contact (sliding). AISI A2 tool steel vs. UNS C95500 aluminium bronze (as-cast or precipitation hardened). Wear mechanisms identified by failure analysis on real components after field operation. Lab tests for assessing influence of applied load, sliding speed and bronze microstructure. Abstract: This study focuses on components for a pressing device involved in a sliding contact. In particular, the tribosystem consists of a pin (AISI A2 tool steel) and a guide plate (UNS C95500 aluminium bronze) coupled under a counterformal line contact. Firstly, the main wear mechanisms in the pin/guide plate contact were identified by failure analysis on real components after field operation, in order to define the conditions for lab-scale dry sliding tests (block-on-ring). Adhesive wear of bronze (leading to material transfer on steel) and two-body abrasion due to hard carbides from tool steel were the main wear mechanisms in field operation. Secondly, lab-scale tests were carried out for studying the influence of (i) applied load, (ii) sliding speed and (iii) bronze microstructure (as-cast condition or precipitation hardened) on tribological behavior. Tribological laboratory tests showed that the coefficient of friction of the bronze/steel couple was more influenced by applied load and sliding speed than by bronze heat treatment conditions. The wear behavior of bronze is mainly influenced by its work hardening capacity as well as by its ability to form a stable and protective copper oxide surface layer.